PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI SMA KELAS X BERBASIS SCIENCE, TECNOLOGY, ENGINEERING, ARTS, AND MATHEMATICS (STEAM) TERINTEGRASI LITERASI SAINS - Wawan Muliawan; Sarwati Sarwati; Heni Andriyana (Jurnal Perspektif Pendidikan, 2022)
This study aims to determine the validity, practicality, and effectiveness of biology modules based on STEAM integrated scientific literacy developed on environmental change material for class X. This type of research is development, using the borg and borg model. Among them are research and information gathering, planning stage, development stage, initial trial stage, and revision stage. The data collection technique used in this study in the form of tests and test questionnaires was used to obtain the effectiveness of the module and questionnaires were used to obtain the value of validity and practicality. The data collection instrument used in this study was an instrument to measure the validity of the module in the form of a material expert validation sheet and a design expert validation sheet. Instruments to measure the practicality of the module are in the form of teacher response questionnaires and student response questionnaires. The instrument to measure the effectiveness of the module is in the form of a Learning Outcome Test (THB). Data analysis in this study used instrument validity, module practicality, and effectiveness analysis. The results of the analysis of the validity of the material expert are 0.84 with valid criteria, the results of the analysis of the validity of the design experts are 0.93 with very valid criteria, the results of the practicality analysis of the teacher's response are 3.5 with very practical criteria, the results of the practicality analysis of student